Molecular response to imatinib mesylate of Brazilian patients with chronic myeloid leukemia - Vieira-Mion,Ana Lucia (2017)
Abstract Background Imatinib mesylate has revolutionized the treatment of chronic myeloid leukemia leading to significant reductions of BCR-ABL1 transcript levels in peripheral blood. Objective To evaluate the response to imatinib mesylate treatment (400 mg/day) in Brazilian patients in the chronic phase of chronic myeloid leukemia monitored by quantitative real time polymerase chain reaction. Methods Between October 2002 and October 2010, 3169 peripheral blood samples were collected from 1403 patients from 3 to 5 months, 6 to 11 months, 12 to 17 months, 18 to 23 months and ≥24 months after beginning imatinib treatment. Eighty-two patients had samples available and analyzed for all time intervals. BCR-ABL1 quantification was performed by quantitative real time polymerase chain reaction using the ABL1 gene as the control. Results of the BCR-ABL1 ratio as a percentage were reported by the international scale (IS) using the laboratory conversion factor (0.51). Results In the first interval, 80.8% of patients achieved the optimal response (BCR-ABL1 IS ≤ 10%). In the second period, 69.1% achieved optimal response (BCR-ABL1 IS ≤ 1%) and, between 12 and 17 months, 47.3% achieved major molecular response (BCR-ABL1 IS ≤ 0.1%). Conclusions The results of this retrospective study show that the response to imatinib treatment (400 mg/day) of Brazilian patients in the chronic phase of chronic myeloid leukemia is within the expected profile when compared to patients reported in international prospective randomized studies.